Imunopatologia da dengue: receptores de quimiocinas CC e células iNKT - Rodrigo Guabiraba Brito (2010)
Dengue virus (DENV), a mosquito-borne flavivirus, is a serious public health problem in many tropical countries. Immune mechanisms involved in the pathogenesis of DENV infection are not fully elucidated. Recent clinical data showed an association between levels of different CC chemokines in plasma and severity of dengue. In this regard, we evaluated the role of CC chemokine receptors CCR1, CCR2 and CCR4 in dengue infection using KO mice for these receptors. Furthermore, we assessed the in vivo contribution of invariant Natural Killer T (iNKT)cells, non-conventional áâ T lymphocytes, to the host response using a mouseadapted DENV-2 strain that causes a disease resembling severe dengue infection. Infected C57/Bl6 mice (WT) presented clinical disease and tissue damage, including thrombocytopenia, hemoconcentration, increased levels of transaminases and proinflammatory cytokines, and lethality. CC chemokines, such as CCL2, CCL3 and CCL5, are strongly produced in spleen and liver of WT mice. CCR1-/- mice had a mildphenotype with disease presentation and lethality similar to those of WT mice. In CCR2-/- mice, lethality, liver damage, levels of IL-6 and IFN-ã, and leukocyte activation were attenuated. However, thrombocytopenia, hemoconcentration and systemic TNF-á levels were similar to infected WT mice. CCL17, a CCR4 ligand, is produced upon infection. In CCR4-/- mice, lethality, tissue injury and systemic inflammation were markedly decreased. Despite differences in disease presentation in CCR-deficient mice, there were no significant differences in viral load. Splenic andhepatic iNKT cells became activated and produce IFN-ã upon infection. Mice deficient in iNKT cells (Já18-/-) are highly resistant to the infection when compared to WT animals. The phenotype was partially recovered by adoptive transfer of iNKT cells to Já18-/-animals. Já18-/- mice presented decreased systemic and local inflammatory responses, with lower levels of IL-6, IFN-ã and CXCL1, reduced liver injury and diminished activation of NK cells and neutrophils. Viral load in spleen and liver was also lower in Já18-/- mice relative to WT mice. áGalCer treatment and CD1dablation had no effects in disease progression. In conclusion, CC chemokine receptors have discrete roles in DENV-2 and endogenous iNKT cell activation during DV infection contributes to the systemic and local inflammatory responses that lead to shock and death, suggesting that CC chemokine receptors and iNKT cells may be associated to the inflammatory response involved in dengue shock syndrome in mice.